1996
DOI: 10.1002/aic.690420108
|View full text |Cite
|
Sign up to set email alerts
|

Transport of n‐paraffins in zeolite T

Abstract: Mass transport of n-heptane, n-nonane, and n-dodecane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Figure 9. Diffusion coefficients as a function of chain length at various temperatures in ERI-type zeolite: (a) silica simulation results; (b) experimental results of Gorring on a potassium-exchanged OFF/ERI intergrowth, 2 Cavalcante et al, 12 and Magalhães et al 13 Error bars on the simulation data are only shown when larger than the symbol size.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 9. Diffusion coefficients as a function of chain length at various temperatures in ERI-type zeolite: (a) silica simulation results; (b) experimental results of Gorring on a potassium-exchanged OFF/ERI intergrowth, 2 Cavalcante et al, 12 and Magalhães et al 13 Error bars on the simulation data are only shown when larger than the symbol size.…”
Section: Resultsmentioning
confidence: 99%
“…We note that the maximum in the frequency factor corresponds to the minimum of the activation energy and the maximum in the diffusion constant. 2 Cavalcante et al, 12 and Magalhães et al 13 Error bars on the simulation data are only shown when larger than the symbol size.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations